Comparison of Ray Tracing and Monte Carlo Calculation Algorithms for Spine Lesions Treated With CyberKnife - Li, Jun; Zhang, Xile; Pan, Yuxi; Zhuang, Hongqing; Yang, Ruijie (Frontiers in Oncology, 2022)
Purpose: This study attempts to evaluate Ray Tracing (RT) and Monte Carlo (MC) algorithm for CyberKnife treatments of spine lesions and determine whether MC algorithm is necessary for all spine treatment and analyze which sites of spine lesion for which RT algorithm is comparable to MC algorithm. Methods: The CyberKnife is used for stereotactic body radiotherapy for lesions in the cervical spine (30), thoracic spine (50), lumbar spine (30) and sacral spine (15). Dose was calculated using RT and MC algorithms for patients planned with the same beam angles and monitor units. Dose-volume histograms of the target and selected critical structures are evaluated. Results: The average target coverage of prescribed dose with MC algorithms was 94.80%, 88.47%, 92.52% and 93.41% respectively in cervical, thoracic, lumbar and sacral spine. For thoracic spine, RT algorithm significantly overestimates the percentage volume of target covered by the prescribed dose, as well as overestimates doses to organs at risk in most cases, including lung, spinal cord and esophagus. For cervical, lumbar and sacral spine, the differences of the target coverage of prescription dose were generally less than 3% between the RT and MC algorithms. The differences of doses to organs at risk varied with lesion sites and surrounding organs. Conclusions: In the thoracic spine lesions with beams through air cavities, RT algorithm should be limited and verified with MC algorithm, but the RT algorithm is adequate for treatment of cervical, lumbar and sacral spine lesions without or small amount of beams passing through the lungs.